The principle of typicality as limit the Punitive State (Comments on Article 10 of the Colombian Penal Code) (2013)
The first paragraph of Article 10 of the Colombian Criminal Code (Act 599 of 2000) establishes a rule governing the so-called principle of typicality, mandating that the criminal law enshrines unequivocally and clearly expresses the basic structural featu